Risk and prognosis of second primary malignancies in patients with follicular lymphoma in the era of rituximab: A population study based on the SEER database - Ying Tian; Wanxi Yang; Juan Xu; Yuanxiao Li; Wenjiao Tang; Caigang Xu (PLoS ONE, 2025)
Objective Follicular lymphoma (FL) patients have achieved favorable long-term survival since the introduction of rituximab. However, the development of second primary malignancies (SPMs) indicates a poor survival prognosis for FL patients, and large-scale studies in this field remain limited. This study investigates the prognostic factors for FL patients in the rituximab era, as well as the clinical characteristics, risk factors, and prognosis for patients who developed SPMs. Methods From 2000 to 2020, a total of 33,104 patients with pathologically confirmed FL were identified within the Surveillance, Epidemiology, and End Results (SEER) database. Competing-risk regression analysis was used to assess prognostic factors for lymphoma-specific survival (LSS), risk factors for developing SPMs, and prognosis in FL patients. Results Multivariate analysis identified age ≥ 40 years, Black race, unmarried status, non-urban residence, nodal lymphoma presentation, Grade 3 histology, advanced Ann Arbor stage, and B symptoms as independent adverse prognostic factors for both overall survival (OS) and LSS. Chemotherapy as initial treatment was associated with inferior LSS in FL patients. Protective factors for OS and LSS included female sex, higher income, diagnosis post-2005, diagnosis-to-treatment intervals >1 month, and receipt of radiotherapy or surgery. SPMs correlated with reduced LSS risk in FL patients. Elevated SPM incidence among patients aged>40years, and non-Hispanic ethnicity, while reduced SPM risks were observed in females, unmarried patients, those receiving non-radiotherapy initial treatment, Grade 3 cases, and patients diagnosed during 2015–2019. Notably, FL patients aged >60 years, unmarried, and those diagnosed post-2010 demonstrated heightened OS risk following SPM development. Conversely, initial radiotherapy conferred protective effects against both OS and LSS in patients with SPMs. Conclusion In this study, we conducted a large, population-based analysis across the United States to identify risk factors for the development of SPMs and to delineate prognostic indicators for FL patients in the context of rituximab therapy, along with the clinical characteristics, risk factors, and prognostic features associated with SPMs. These findings have translational implications for risk-adapted surveillance. Future studies should validate predictive models across diverse healthcare settings, elucidate molecular mechanisms of SPM pathogenesis in FL, and evaluate targeted screening interventions through prospective trials.